THE IMPORTANCE OF INNOVATIVE ECONOMIC MEASURES IN FORMING THE COMPETITIVE ENVIRONMENT - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: this article examines the importance of innovative economic measures in the formation of a competitive environment. The article also examines the essence of  the  competitive  environment  in  the  country's  economy  and  the  importance  of economic  measures  taken  in  its  formation,  the  effectiveness  of  privileges  and preferences  that  determine  the  directions  of  economic  development  in  a  market economy, and the priority principles of development programs based on international experience. Reforms aimed at developing a competitive environment at the current stage of the Uzbek economy are studied.